Comparative microbial quality of jedi drinks sold in two major cities in Nigeria (2010)
The microbial quality of ten samples of Jedi herbal preparations sold for the treatment of anal fistula in major motor parks of Sagamu and Ibadan, both in Nigeria was studied and compared. Phytochemical analysis of the samples revealed that all the samples contained Saponins and Tannins. Alkaloids and cardenolides were also present to varying extent. These secondary metabolites are known to be responsible for the prevention of anal fistula. 100% contained Pseudomonas aeruginosa, 80% from Sagamu contained Klebsiella spp; 60% from Ibadan contained Bacillus spp, 30% of the samples contained Staphylococcus aureus and 70% contained fungi. Antibiotic sensitivity patterns revealed that the Gram-negative isolates were most sensitive to ofloxacin, a quinolone antibiotic while the Gram-positive isolates were most sensitive to Streptomycin, an aminoglycoside